How anxious is too anxious? State and trait physiological arousal predict anxious youth’s treatment response to brief cognitive behavioral therapy - Caitlyn C. McCormack; Rebekah J. Mennies; Jennifer S. Silk; Lindsey B. Stone (BMC Psychology, 2020)
Abstract Background Exposure therapy is the gold standard for treating childhood anxiety, yet not all youth improve. Children do not always have insight on their distress, which can limit the utility of self-reported units of distress (SUDS) during exposures. Physiological assessment provides an objective means of monitoring emotional arousal. Electrodermal activity (EDA) in particular indexes sympathetic nervous system arousal which is heavily linked to anxiety. The aim of the current study was to examine the feasibility and utility of incorporating EDA assessment in an in-session exposure. We examined concordance between EDA and SUDS, and whether either predicted treatment response. Methods Thirty-four youth who met DSM-5 criteria for generalized, separation, and/or social anxiety disorder completed brief CBT (8 sessions) and completed a survey on trait physiological arousal. EDA and SUDS were collected from 18 youth (9 female, ages 9–14) during a mid-treatment exposure. Changes in anxiety severity were examined post-treatment. Results SUDS were not correlated with trait or state physiological arousal. There was a large association between heightened sympathetic arousal and poorer post-treatment response. Similarly, SUDS indices of greater fear activation and habituation were associated with poorer post-treatment response with a small to moderate effect size. Supplemental analyses among the full sample aligned: trait physiological arousal predicted poorer treatment response. Conclusions The lack of concordance between sympathetic arousal and SUDS indices highlights the limitations of relying solely on SUDS with pediatric populations. EDA provided unique data on youth’s distress during exposures. Thus, results indicate that physiological assessment may exhibit clinical utility for aiding clinicians in monitoring youth’s progress in exposure therapy. Trial Registration ClinicalTrials.gov Identifier: NCT02259036 .